Iris Kelly doesn't date - Blake, Ashley Herring (Blake, Ashley Herring, Bright Falls, 2023)
"Everyone around Iris Kelly is in love. Her best friends are all coupled up, her siblings have partners that are perfect for them, and her parents are still blissfully married. And she's happy for all of them, truly. Iris doesn't want any of that-dating, love, romance. She'll stick to her commitment-free hookups, thanks very much, except no one in her life will just let her be. Everyone wants to see her settled down, but she holds firmly to her no dating rule. There's only one problem-Iris is a romance author facing an imminent deadline for her second book, and she's completely out of ideas. Perfectly happy to ignore her problems as per usual, Iris goes to a bar in Portland and meets a sexy stranger, Stefania, and a night of dancing and making out turns into the worst one-night stand Iris has had in her life. To get her mind off everything, Iris tries out for the lead role in a local play, a queer retelling of Much Ado About Nothing, but comes face-to-face with Stefania, whose real name turns out to be Stevie. Desperate to save face in front of her friends, Stevie asks Iris to play along as her girlfriend. Iris is shocked, but when she realizes the arrangement might provide her with some much-needed romantic content for her book, she agrees. As the two women play the part of a happy couple, lines start to blur, and they're left wondering who will make the real first move..."--